Study on applicability of radial-outflow turbine type for 3 MW WHR organic Rankine cycle. (September 2017) - Maksiuta, Dmytro; Moroz, Leonid; Burlaka, Maksym; Govoruschenko, Yurii
Abstract: The article presents the results of study on the reasonability of using radial-outflow turbines in ORC. Peculiarities of radial-outflow turbine design utilizing modern design technologies and application to ORC was considered in the first part of the paper. The second part of the paper describes the selection process of the best turbine type for a 3 MW WHR ORC power unit for an internal combustion engine. The selection was performed among different turbine types, like radial-inflow, axial and radial-outflow turbines which were designed with given boundary conditions. The advantages and disadvantages of their application were shown. Eventually, the recommendations regarding application of different turbine types for a 3 MW WHR Organic Rankine Cycle were given. For this particular cycle design, turbines of radial-outflow type were chosen. Their application enables the increase of mechanical output power by 11 % compared to original radial-inflow turbines.